SEJARAH TARI BUBU DI DESA SANDAI KIRI KECAMATAN SANDAI KABUPATEN KETAPANG - Wahyuni, Sinta Seri; Ismunandar, Ismunandar; Aditya, Mega Cantik Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is motivated by uniqueness Another which can move when recited poems and spells contained in the Bubu Dance in Sandai Kiri Village, Sandai District, Ketapang Regencyand peel back the history of the beginningother magic that can move and created dance as an accompaniment with the aim of making it more entertaining. This study aims to describe the history of the Bubu Dance in Sandai Kiri Village, Sandai District, Ketapang Regency. This study uses a descriptive method in a qualitative form, assisted by historical and anthropological approaches. Data collection techniques used in the form of interview techniques, documentation techniques, and documentation study techniques. From the results of this research, the history of the Bubu Dance begins with the story of Si Lokan, who had an illness and finally recovered because he entered the Bubu while composing and creating a poem about his father and mother. The poems and mantras sung in the show contain recitations of the holy verses of the Koran. There was a change in the show, at first it was artother accompanied by four female dancers, but now the only ones left in the show are the handler andother. Along with developments, the performance form of the Bubu Dance was eventually recognized as a traditional game originating from Sandai Village.